2020
DOI: 10.1590/1678-4324-2020180679
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Agrobacterium rhizogenes-induced Hairy Root Formation in Selaginella bryopteris: a Pteridophyte Recalcitrant to Genetic Transformation

Abstract:  A. rhizogenes (strain LBA1334) co-cultivation with explants (root, rhizophore, stem portion near the root, and stem with intact fronds) of S. bryopteris led to induction of hairy roots after 6 days of infection in case of 48 h co-cultivation only.  Out of different media like MS, SHFR (Stage Hog Fern Root) and KNOP's, SHFR showed good response in transformation as well as propagation.  PCR with rol A and vir C gene specific primers confirmed the Ri T-DNA integration in induced hairy roots.  Addition of TD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…For example, the transformation efficiency of Selaginella bryopteris was enhanced TDZ (2 mg/L) to generate hairy roots. 67…”
Section: The Role Of Thidiazuron In Exploiting Hairy Root Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the transformation efficiency of Selaginella bryopteris was enhanced TDZ (2 mg/L) to generate hairy roots. 67…”
Section: The Role Of Thidiazuron In Exploiting Hairy Root Culturesmentioning
confidence: 99%
“…Hairy root cultures can produce certain medicinally and commercially when treated with TDZ. For example, the transformation efficiency of Selaginella bryopteris was enhanced TDZ (2 mg/L) to generate hairy roots 67 …”
Section: Applications Of Thidiazuron In Plant Tissue Culturementioning
confidence: 99%
“…Chung and coauthors (2016) used jasmonic acid (JA) and salicylic acid (SA) elicitors to enhance biomass accumulation and phenolic compound production in hairy root cultures of Momordica charantia L.. Their results revealed that cultures supplemented with 100 μM JA and SA can significantly enhance the production of phenolic compounds in compared to control cultures [19]. In recent years, there is a growing interest to biotechnological methods such as liquid and hairy root cultures through A. rhizogenes for enhancement of secondary metabolites production in medicinal plants [20][21][22].…”
Section: Introductionmentioning
confidence: 99%